Comparable studies of rainfed upland winter rice (Oryza sativa) cultivars for drought tolerance - DEKA, MANABENDRA; BARUAH, K K (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1995-96 to compare ten upland winter season (rabi) rice (Oryza sativa L.) cultivars amongst themselves for drought tolerance based on some physiological parameters. The seeds were first subjected to moisture stress to study the effect of drought on seed germination. Five levels of moisture stress (0,-3.0,-5.0,-7.5 and-10.0 bar) treatment were given with 'PEG 6000'.Â  The per sent germination decreased with increase in intensity of stress in all the cultivars. Amongst the cultivars'Iharsal Ahu' and 'Maibee II' recorded better germination under stress. Though relative leaf water content, leaf area, root and shoot dry weight decreased significantly under stress, cultivars 'Iharsal Ahu' and 'Maibee II' performed better under stress. The cultivars also differed significantly in respect of leaf chlorophy II, proline, nitrate reductase activityÂ  and nitrogen, phosphorus and potassium content under stress and non-stress condition. 'Iharsal Ahu' and 'Maibee II'showed better results under stress indicating their to lerance to moisture stress.